A Structurally Characterized CuIII Complex Supported by a Bis(anilido) Ligand and Its Oxidative Catalytic Activity. Issue 56 (11th August 2017) - Kochem, Amélie; Molloy, Jennifer K.; Gellon, Gisèle; Leconte, Nicolas; Philouze, Christian; Berthiol, Florian; Jarjayes, Olivier; Thomas, Fabrice
Abstract: Three copper(II) complexes of the ( R, R )‐ N, N ′‐bis(3, 5‐di‐ tert ‐butyl‐2‐aminobenzylidene)‐1, 2‐diaminocyclohexane ligand, namely[Cu( N L)], [Cu( N LH)] + and[Cu( N LH2 )] 2+, were prepared and structurally characterized. In[Cu( N LH2 )] 2+ the copper ion lies in an octahedral geometry with the aniline groups coordinated in equatorial positions. In[Cu( N L)] the anilines are deprotonated (anilido moieties) and coordinated to an almost square‐planar metal ion. Complex[Cu( N L)] displays two oxidation waves at E 1/2 ox, 1 =−0.14 V and E 1/2 ox, 2 =0.36 V vs. Fc + /Fc in CH2 Cl2 . Complex[Cu( N LH2 )] 2+ displays an irreversible oxidation wave at high potential (1.21 V), but shows a readily accessible and reversible metal‐centered reduction at E 1/2 red =−0.67 V (Cu II /Cu I redox couple). Oxidation of[Cu( N L)] by AgSbF6 produces[Cu( N L)] (SbF6 ), which was isolated as single crystals. X‐ray structure analysis discloses a contraction of the coordination sphere by 0.05 Å upon oxidation, supporting a metal‐centered process. Complex[Cu( N L)] (SbF6 ) displays an intense NIR band at 1260 nm corresponding to an anilido‐to‐copper(III) charge transfer transition. This compound slowly evolves in CH2 Cl2 solution towards[Cu( N LH)] (SbF6 ), which is a copper(II) complex comprised of both anilido and aniline groups coordinated to the metal center. The copper(III) complex[Cu( N L)] (SbF6 ) is an efficient catalyst for benzyl alcohol oxidation, with 236 TON in 24 h at 298 K, without additives other than oxygen and a base. Abstract : Good things come in threes : The anilido donors make the Cu II complex easy to oxidize. The contraction of the coordination sphere observed after one‐electron oxidation reveals that the oxidized species is a Cu III bis(anilido) complex. It displays a peculiar signature in its electronic spectrum, which is an intense NIR band corresponding to the anilido‐to‐copper charge transfer transition. The copper(III) complex catalyzes the aerobic oxidation of benzyl alcohol to benzaldehyde.